Understanding low colorectal cancer screening uptake in South Asian faith communities in England – a qualitative study - Palmer, Cecily K. (BMC Public Health, 2015)
BACKGROUND: Colorectal cancer screening uptake within the South Asian population in England is approximately half that of the general population (33 % vs 61 %), and varies by Muslim (31.9 %), Sikh (34.6 %) and Hindu (43.7 %) faith background. This study sought to explore reasons for low uptake of CRC screening in South Asian communities and for the variability of low uptake between three faith communities; and to identify strategies by which uptake might be improved. METHODS: We interviewed 16 ‘key informants’ representing communities from the three largest South Asian faith backgrounds (Islam, Hinduism and Sikhism) in London, England. RESULTS: Reasons for low colorectal cancer screening uptake were overwhelmingly shared across South Asian faith groups. These were: limitations posed by written English; limitations posed by any written language; reliance on younger family members; low awareness of colorectal cancer and screening; and difficulties associated with faeces. Non-written information delivered verbally and interactively within faith or community settings was preferred across faith communities. CONCLUSIONS: Efforts to increase accessibility to colorectal cancer screening in South Asian communities should use local language broadcasts on ethnic media and face-to-face approaches within community and faith settings to increase awareness of colorectal cancer and screening, and address challenges posed by written materials.